Ketahanan Beberapa Varietas Kedelai Terhadap Nematoda Puru Akar (Meloidogyne incognita) - A Muin Adnan (Buletin Hama dan Penyakit Tumbuhan, 2000)
Resistance of 19 soybean varieties to the root-knot nematode (Meloidogyne incognita) was evaluated in the green-house. One-week old seeding in a plastic bag containing 4 liters soil of Segunung Andosol type, was infested with 500 second stage juveniles (L2) per 1000 cm cubic of soil. The experiment was arranged in a completely randomiz-ed design with three replication. Based on the reproductive index of M.incognita, two varieties (Wilis and Ringgit) were moderately resistant, 14 varieties were slightly resistant and three varieties (Muria, Malabar, and Lakon) were susceptible to M.incognita. The productive index of M.incognita on the varieties that were moderately resistant, slightly, and susceptible were 12.75 - 23.65, 25.48 - 42.88, and 50.99 -58.83 % respectively